"The women, they maltreat them… therefore, we cannot assure that the future society will be good": Male perspectives on gender-based violence: A focus group study with young men in Haiti. Issue 7 (2nd July 2016) - Gabriel, Naïka C.; Sloand, Elizabeth; Gary, Faye; Hassan, Mona; Bertrand, Desiree R.; Campbell, Jacquelyn
ABSTRACT: The purpose of this study was to explore the perceptions of violence against women (VAW) held by Haitian men to gain a better understanding of why VAW occurs. Women in Haiti have experienced significant violence, both before and following the 2010 earthquake. Fifteen men aged 26 to 47 participated in a focus group. The data revealed three themes: men's beliefs about VAW and its context, factors influencing VAW, and recommended interventions. When approaching VAW, men must be part of the collective effort. Their insights are valuable when planning and implementing interventions to decrease VAW in Haiti and worldwide.